Molapi Saronde sebagai Pengikat Kekerabatan pada Hui Mopotilandahu di Kecamatan Telaga Jaya - Hangga, Ancul; Nurlia Djafar; Ode Karlan (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2026)
The development of modernization and globalization has brought significant impacts on changes in social and cultural values within society, including traditional customs that have been passed down from generation to generation. The Gorontalo community, despite undergoing various transformations, continues to preserve several customary traditions, one of which is Molapi Saronde, performed in the Hui Mopotilandahu procession as part of the traditional wedding ceremony. This study aims to examine the role of the Molapi Saronde dance as a means of strengthening kinship ties within the Hui Mopotilandahu procession in Telaga Jaya District, Gorontalo Regency. This research employs a qualitative approach, with data collection techniques including observation, in-depth interviews with traditional leaders and cultural practitioners, and documentation. Data were analyzed through the stages of data reduction, data presentation, and conclusion drawing. The findings indicate that Molapi Saronde functions not only as a form of ritual artistic performance but also plays an important social role in strengthening kinship relationships between the families of the prospective bride and groom. The dance embodies values of togetherness, harmony, religiosity, education, and aesthetics, which are reflected in the involvement of families and the wider community in the customary procession. Molapi Saronde serves as a medium of social interaction that affirms acceptance, solidarity, and harmony between families. The implications of this study emphasize the importance of preserving Molapi Saronde as a local cultural heritage that maintains cultural identity and strengthens social bonds within Gorontalo society amid the dynamics of contemporary change.